A Phase 2 open label study of ledipasvir/sofosbuvir for 12 weeks in subjects with hepatitis B virus infection. Issue 1 (12th September 2022) - Price, Angie S.; Nelson, Amy K.; Ghosh, Alip; Kottilil, Shyamasundaran; Chua, Joel V.
Abstract: Retrospective data showed that when we administered ledipasvir/sofosbuvir (LDV/SOF) to patients with hepatitis B and C coinfection, there was a modest reduction in hepatitis B surface antigen (HBsAg). Therefore, we hypothesize that similar HBsAg reduction can be seen in hepatitis B virus (HBV) monoinfected subjects. Primary and secondary efficacy endpoints are the decline in HBsAg and HBV DNA at Week 12 from baseline, respectively. We conducted an open‐label Phase 2 pilot study to evaluate the safety, tolerability, and antiviral activity of LDV and/or SOF for HBV. Eligible subjects were either suppressed on antivirals (Group B) or inactive chronic HBV (Group A, C, D). Group A and B received LDV/SOF. Group C and D received SOF 400 mg and LDV 90 mg, respectively. All subjects completed the study, and all related adverse events (AEs) were mild. No discontinuations due to AEs or hepatitis flare occurred. At Week 12, HBsAg decline (log10 IU/ml) was similar between Group A (0.399) and B (0.400), less in Group C (0.207), and none in Group D, and there was HBV DNA decline in the inactive chronic HBV groups. LDV and SOF are safe and well tolerated when given to chronic hepatitis B subjects and have modest antiviral activity, particularly when given in combination.